The changes in health-related quality of life after attending cardiac rehabilitation: A qualitative systematic review of the perspective of patients living with heart disease - Amineh Rashidi; Lisa Whitehead; Helena Halton; Lisa Munro; Ian Jones; Lisa Newson (PLoS ONE, 2025)
Background Although the benefits of engaging in cardiac rehabilitation are well established, patient perceptions of the changes in their health-related quality of life are poorly documented. This systematic review synthesized qualitative studies on patients’ perspectives of change in their health-related quality of life after attending cardiac rehabilitation. Objective To identify and synthesize the best available evidence on the perspective of patients living with heart disease about the changes in their health-related quality of life after attending cardiac rehabilitation. Methods Eight databases were used to identify relevant papers published in English and peer-reviewed, and no date restrictions were considered for the search. This systematic review followed the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines. The Joanna Briggs Institute (JBI) Critical Appraisal Checklist was used to appraise the quality of each paper, and two independent reviewers conducted it. A meta-aggregation approach was used to synthesize the findings of the included studies. Results The search identified 10813 titles. Thirty-five full-text papers were reviewed after duplicates were removed, and the titles and abstracts were reviewed. Thirteen papers were retained for data synthesis. The synthesized findings were divided into three categories: building healthier habits, peer interaction, and improving mental health. Conclusion This review demonstrates the positive changes in health-related quality of life for those patients engaged in cardiac rehabilitation. Peer interaction with other patients improved both mental and physical health. This review indicated that adopting healthier habits, including healthy eating and regular physical activity, had substantial benefits in formulating healthy behavior. The role of peers in supporting the development of a healthy lifestyle appears to be an understudied avenue and has potential for development.